2016
DOI: 10.2147/ceor.s122177
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of combination antifungal therapy with voriconazole and anidulafungin versus voriconazole monotherapy for primary treatment of invasive aspergillosis in Spain

Abstract: ObjectiveAccording to a recent randomized, double-blind clinical trial comparing the combination of voriconazole and anidulafungin (VOR+ANI) with VOR monotherapy for invasive aspergillosis (IA) in patients with hematologic disease or with hematopoietic stem cell transplant, mortality was lower after 6 weeks with VOR+ANI than with VOR monotherapy in a post hoc analysis of patients with galactomannan-based IA. The objective of this study was to compare the cost-effectiveness of VOR+ANI with VOR, from the perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…6 IMDs have a high economic impact as well. 1,7,8 In line with available data in the website of the Spanish Ministry of Health RAE-CMBD (Registro Atención Especializada-Conjunto Mínimo Básico de Datos), 9 length of stay for IA in Spain in 2017 was 54.20 days and the mean associated costs were 18,235€; regarding IM the length of stay was 70 days and the mean costs were 24,020€.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…6 IMDs have a high economic impact as well. 1,7,8 In line with available data in the website of the Spanish Ministry of Health RAE-CMBD (Registro Atención Especializada-Conjunto Mínimo Básico de Datos), 9 length of stay for IA in Spain in 2017 was 54.20 days and the mean associated costs were 18,235€; regarding IM the length of stay was 70 days and the mean costs were 24,020€.…”
Section: Introductionmentioning
confidence: 68%
“…For instance, according to a study analysed by the FDA, a delay of 6 days in the initiation of treatment, increased mortality rates up to almost two times, from 48.6% to 82.9% 6 . IMDs have a high economic impact as well 1,7,8 . In line with available data in the website of the Spanish Ministry of Health RAE‐CMBD (Registro Atención Especializada‐ Conjunto Mínimo Básico de Datos), 9 length of stay for IA in Spain in 2017 was 54.20 days and the mean associated costs were 18,235€; regarding IM the length of stay was 70 days and the mean costs were 24,020€.…”
Section: Introductionmentioning
confidence: 71%
“…(12) Although clinical data on voriconazole in combination with echinocandins for the treatment of CNS-IA are still limited, some studies have indicated that this combination can improve the survival outcomes of patients with pulmonary-IA infections. (13) Considering that the patient in the present had a disseminated Aspergillus infection involving multiple organs, we adopted a treatment regimen of voriconazole in conjunction with caspofungin. Although the patient presented herein eventually died, his clinical symptoms and imaging examinations after one week of this combined treatment indicated that this treatment regimen might be effective against the A. nidulans strain.…”
Section: Discussionmentioning
confidence: 99%